Uterine arteriovenous malformation - Patki, Sneha S.; Dabade, Trishula; Kumar, Vijay (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Uterine arteriovenous malformation (AVM) is a rare condition. It can become life threatening due to the profuse bleeding with which patients may present. This case report presents a case of a 40-year-old lady who presented with repeated episodes of bleeding per vaginum after a dilatation and evacuation for an induced abortion. Ultrasound along with Doppler showed AVM in the anterior body of the uterus which was eventually confirmed by Magnetic Resonance Imaging. With no desire to preserve future fertility, our patient underwent a laparoscopic assisted vaginal hysterectomy successfully. The diagnosis was confirmed on histopathology.